Hydration, kidney injury and clinical outcome - El-Sharkawy, Ahmed M (2016)
Studies in health care professional (HCPs) have demonstrated a high prevalence of dehydration, which has been linked with morphological brain changes as well as cognitive impairment in other groups. Moreover, many age-related pathophysiological changes result in increased susceptibility to fluid and electrolyte imbalance, rendering older adults vulnerable to dehydration which may be associated with poor outcome.